Interventional bronchoscopy for chronic obstructive pulmonary disease: more than a pipe dream. Issue 6 (11th August 2021) - Carew, Alan M; Williamson, Jonathan P; Farah, Claude S; Saghaie, Tajalli; Phillips, Martin; Ing, Alvin
Summary: Endoscopic lung volume reduction (ELVR) is recognised in both national and international expert guidelines as one of the few additive treatments to benefit patients with advanced chronic obstructive pulmonary disease (COPD) who are otherwise receiving optimal medical and supportive care. Despite these recommendations and a growing evidence base, these procedures are not widely offered across Australia and New Zealand, and general practitioner and physician awareness of this therapy can be improved. ELVR aims to mitigate the impact of hyperinflation and gas trapping on dyspnoea and exercise intolerance in COPD. Effective ELVR is of proven benefit in improving symptoms, quality of life, lung function and survival. Several endoscopic techniques to achieve ELVR have been developed, with endobronchial valve placement to collapse a single lobe being the most widely studied and commonly practised. This review describes the physiological rationale underpinning lung volume reduction, highlights the challenges of patient selection, and provides an overview of the evidence for current and investigational endoscopic interventions for COPD.